Penggunaan Diksi Pada Bak Truk Di Sekitar Jalan Ringroad Mojosongo Sebagai Bahan Ajar Pelajaran Bahasa Indonesia Di SMP - Saputri, Nia, Prof. Dr. Markamah, M.Hum (2016)
This study has three objectives (1) to describe the use of diction on the tailgate around the Mojosongo ringroad, (2) to describe what the phrase of diction on the tailgate around the Mojosongo ringroad, (3) to describe diction on the tailgate around the road Mojosongo ringroad as a materials learning of Indonesian language in junior high. This study used descriptive qualitative method. Object under study is diction and expression of intent on the tailgate around the nets Mojosongo ringroad. The data in this study are words, phrases, and sentences written containing no tailgate diction. Source of research data is a photo or picture writing on the back of the truck. Data collection techniques that interview, see the note, and documentation. The validity of the data using triangulation techniques theory. Data analysis technique used is a basic technique for direct element. Advanced techniques in this study using techniques expand. The results of this research there are three things. (1) The use of diction on the tailgate around the Mojosongo ringroad, focused on common words and diction special word. The dominant diction used on the truck is a special word diction. Diction common words found 11 words. Diction special word found 29 words. (2) The purpose of the expression on the tailgate around the Mojosongo ringroad grouped into four, namely intent expression giving information, ban, ordered, and orders. (3) Diction on the tailgate around the Mojosongo ringroad can be used as a materials learning of Indonesian language in junior class VII syllabus in accordance with the curriculum of 2013. Core Competence 3. Understanding knowledge (factual, conceptual and procedural) by curiosity about science, technology, art, culture, associated phenomena and events looking eyes. Basic Competency 3.1 Understanding text observation, descriptive feedback, exposition, explanation, and short stories through oral and written. Keyword:diction, expression, tailgate